Butyric acid ameliorates PCOS-related reproductive dysfunction through gut-brain-ovary axis signaling and ovarian steroidogenic factor activation - Feng, Xueping; Xiao, Juan; Wang, Decai; Fu, Xianzhao; Gao, Jie; Jiang, Minli; Li, Jin; Jiang, Lihe; Liang, Xingwei; Huang, Yanna; Jiang, Qinyang (Frontiers in Endocrinology, 2025)
BackgroundButyric acid deficiency is implicated in polycystic ovary syndrome (PCOS), as evidenced by reduced levels in both clinical and preclinical models. Sodium butyrate (NaBu),a butyric acid substitute, has demonstrated therapeutic potential through gut-brain axis modulation, anti-inflammatory effects, and reproductive function protection. This study investigates NaBu’s mechanistic role in PCOS pathophysiology.MethodsPCOS rats received lipo-coated NaBu diet for three weeks. Systemic and tissue analyses included: serum hormone profiling, lipid metabolism assessment, ovarian/colonic histopathology, Short-chain fatty acids (SCFAs) analysis, and proteomics analysis. Primary granulosa cell cultures with lentiviral transfection elucidated molecular mechanisms. Reproductive performance was evaluated longitudinally.ResultsTreatment with NaBu in PCOS rats resulted in reduced food intake, inhibited weight gain, improved abnormal lipid metabolism, restored estrus cycles and ovulation, lower serum levels of testosterone (T), insulin (INS), and luteinizing hormone (LH), and higher levels of estradiol (E2) and progesterone (P4). Additionally, NaBu treatment improved the morphology of polycystic ovaries, elevated colonic levels of G protein-coupled receptor 41 (GPR41), peptide tyrosine-tyrosine (PYY), and butyric acid, and enhanced reproductive performance in PCOS rats. Proteomic analysis and cell experiments suggested that upregulation of Cytochrome P450 1b1 (Cyp1b1) may play a crucial role in regulating E2 metabolism and P4 production, potentially contributing to the pathogenesis of PCOS and ovarian dysfunction.ConclusionThese findings indicate that NaBu may exert its regulatory effects on appetite and hormone levels in the hypothalamus through the gut-brain-ovary axis, modulating the expression of ovarian steroidogenic factors, thereby improving follicular development and granulosa cell function, and enhancing reproductive performance.